Pre-Service Teachers’ Perceptions of Blended Learning on Mathematics Learning Based on Gender - Aina Azka; Ayu Faradillah (Universitas Sarjanawiyata Tamansiswa, 2020)
The research aims to analyze pre-service teachers’ perceptions about the application of the blended learning model in mathematics learning. The total research subjects were 254 pre-service teachers from 12 different universities in Indonesia. Furthermore, this research method is a survey with a qualitative approach where data are analyzed using the Rasch Model (WinSteps). The instrument of this study was a questionnaire consisting of 20 statements and divided into four indicators. Based on the wright maps table on WinSteps, women pre-service teachers prefer the blended learning model in learning mathematics than men pre-service teachers. Meanwhile, when viewed in terms of grade, fourth year pre-service teachers like the application of the blended learning model the most. In addition, it is also known that the most disliked thing in understanding mathematics by using blended learning is the difficulty to access assignments online and it requires internet quotas.